Hyponatremia and Oxidative Stress - Benedetta Fibbi; Giada Marroncini; Cecilia Anceschi; Laura Naldi; Alessandro Peri (MDPI AG, 2021)
Hyponatremia, i.e., the presence of a serum sodium concentration ([Na+]) < 136 mEq/L, is the most frequent electrolyte imbalance in the elderly and in hospitalized patients. Symptoms of acute hyponatremia, whose main target is the central nervous system, are explained by the "osmotic theory" and the neuronal swelling secondary to decreased extracellular osmolality, which determines cerebral oedema. Following the description of neurological and systemic manifestations even in mild and chronic hyponatremia, in the last decade reduced extracellular [Na+] was associated with detrimental effects on cellular homeostasis independently of hypoosmolality. Most of these alterations appeared to be elicited by oxidative stress. In this review, we focus on the role of oxidative stress on both osmolality-dependent and -independent impairment of cell and tissue functions observed in hyponatremic conditions. Furthermore, basic and clinical research suggested that oxidative stress appears to be a common denominator of the degenerative processes related to aging, cancer progression, and hyponatremia. Of note, low [Na+] is able to exacerbate multiple manifestations of senescence and to decrease progression-free and overall survival in oncologic patients.